STRUCTURAL EXTRAJUDICIAL ACTION BY THE PUBLIC PROSECUTOR’S OFFICE: TOOLS FOR ADEQUATE SOLUTIONS TO PROBLEMS - de Souza Junior, Joaquim Ribeiro (Seven Editora, 2026)
Brazil’s 1988 Constitution reframed the Public Prosecutor’s Office (MP) as a guardian of the legal order and collective interests, widening its toolbox beyond litigation. This paper analyses four structural extrajudicial instruments available to the MP—inquérito civil (civil inquiry), administrative procedure, recommendation, and term of conduct adjustment—as mechanisms for preventing and resolving collective disputes. Based on doctrinal and normative research, we argue that the ‘resolutive model’, grounded in institutional dialogue and consensus, is better suited to address complex, polycentric conflicts than purely adversarial lawsuits. These instruments foster flexibility, speed and cost‑effectiveness, but their success depends on methodological refinement and internal cultural change. We conclude that structural extrajudicial action represents a promising path towards de‑judicialisation, enhancing the effective protection of fundamental rights and catalysing the transformation of dysfunctional public structures. DOI: https://doi.org/10.56238/sevened2026.008-056